1991
DOI: 10.4038/jnsfsr.v19i2.8156
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Some Chemical Components of Nutmeg (Myristica Fragrans-Houtt) Leaf Directed at Determination of Sex of Seedlings

Abstract: : The essential oil content and the tlc phenolic profiles of the leaves of seedlings, 5 -year old and adult nutmeg, IVyrismfca.f?agnmr plants were studied. Significantly higher essential oil content and the absence of two phenolic spois were observed in female adult plants when m~npared with males. Differences in a -pinene, terpinolene, a -terpinine, myrcene and gemnyi acetate content were also seen. Using other criteria described for the sexing of nutmeg seedlings to identify suspect male and female plants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Phadnis and Choudhary [23] advocated a colorimetric test that they claimed could distinguish sex in approximately two thirds of seedlings while Nayar et al [24] examining the epidermal cells of nutmeg leaf described the different structures of calcium oxalate crystals in seedlings of male and female plants. In a preliminary study, it was indicated that characteristics such as leaf shape, essential oil content and composition and profile of phenolics differ in male and female plants [25]. Contrarily, a study conducted by Mezencev et al [26] confirmed the absence of obvious relationship between the extents of morphological variations and that of changes at the DNA level already reported in rice.…”
Section: Conventional Sex Diagnosticsmentioning
confidence: 83%
“…Phadnis and Choudhary [23] advocated a colorimetric test that they claimed could distinguish sex in approximately two thirds of seedlings while Nayar et al [24] examining the epidermal cells of nutmeg leaf described the different structures of calcium oxalate crystals in seedlings of male and female plants. In a preliminary study, it was indicated that characteristics such as leaf shape, essential oil content and composition and profile of phenolics differ in male and female plants [25]. Contrarily, a study conducted by Mezencev et al [26] confirmed the absence of obvious relationship between the extents of morphological variations and that of changes at the DNA level already reported in rice.…”
Section: Conventional Sex Diagnosticsmentioning
confidence: 83%